Trauma pneumonectomy: A narrative review. (October 2017) - Phillips, B.; Turco, L.; Mirzaie, M.; Fernandez, C.
Abstract: Purpose: Thoracic injuries are common in both blunt and penetrating trauma. Most thoracic injuries are managed non-operatively, approximately 7–20% undergo thoracotomy. Of the injuries requiring thoracotomy, 1–6% ultimately require pulmonary resection. Wedge resection and lobectomies are well-studied in the literature; however, there is a paucity regarding reports on total pneumonectomy in the setting of trauma. Our objectives were to summarize the evidence supporting the role of trauma pneumonectomy (TP) in the current era and reiterate that despite the associated morbidity and mortality TP is justified in selective cases. Methods: A review of the world's literature was conducted following standard guidelines. Inclusion criteria included those studies reviewing blunt and penetrating trauma to the lungs in adults (age greater than 15 year) that reported mortality rates and outcome measures. Results: The PubMed search yielded 713 studies. Of these, 14 studies included pertinent information on TP. Studies included in this review were published from 1985 to 2017 and involved patient data that was collected from 1972 to 2014. Mortality ranged from 50% to 100% (median 63%; mean 68%). Conclusion: In the setting of severe thoracic trauma, pulmonary resection may be necessary. Less aggressive techniques are options in a stable patient; however, in the setting of ongoing hemorrhage, TP should be considered and expediently conducted. The role of damage control thoracic surgery and related techniques is vitally important in these patients to improve the significant mortality of trauma pneumonectomy. Highlights: Trauma Pneumonectomy (TP) has always been considered a last resort amongst trauma surgeons. Earlier consideration of TP may lead to better outcomes. The literature is clear: with patients in extremis, be aggressive and decisive.